Management of Pediatric Inguinal Hernias in the Era of Laparoscopy: Results of an International Survey - Zani, Augusto; Eaton, Simon; Hoellwarth, Michael; Puri, Prem; Tovar, Juan; Fasching, Guenter; Bagolan, Pietro; Lukac, Marija; Wijnen, Rene; Kuebler, Joachim; Cecchetto, Giovanni; Rintala, Risto; Pierro, Agostino (European Journal of Pediatric Surgery, 2014)
Aim The aim of the study is to present views of pediatric surgeons on the optimal approach to inguinal hernias in children.Methods A questionnaire was submitted to participants of EUPSA-BAPS 2012 and it was returned by 187 responders (85% senior surgeons) from 46 (27 European) countries.Main Results Approximately 80% of the responders work in centers treating more than 100 cases/year. Approximately 79% of the responders routinely perform laparoscopy for other conditions, but of these, only 22% of the responders routinely perform laparoscopic inguinal hernia repair. Open approach is preferred by 83% of the responders. Of these, 79% of the responders favor unilateral approach, 12% of the responders contralateral, and 9% of the responders contralateral laparoscopic exploration via hernial sac. Considered advantages are the less risk of recurrence (66%), less abdominal organ injury (31%), less vas/vessel injury (25%), and speed (16%). Laparoscopic approach is preferred by 17% of the respondents, of whom 58% perform laparoscopy at all ages, 15% only in younger than 1-year-old infants. Approximately 81% of the responders offer laparoscopy to both sexes, and 17% only in girls. Only 15% would do laparoscopy after incarceration. Purse string is the most popular (58%), then laparoscopic-guided percutaneous closure (28%), “flip-flap” (6%), or other techniques (8%). Proficiency is achieved after 50 (14%), 25 (48%), 10 (32%), or 5 (6%) laparoscopic hernia repairs. Considered advantages are less metachronous contralateral hernias (57%), better cosmesis (41%), easier technique (34%), less vas/vessel injury (31%), and less postoperative pain (22%). A total of 50 responders are planning to start laparoscopic hernia repairs.Conclusions Most pediatric surgeons favor open unilateral inguinal hernia repair. The role of laparoscopy in inguinal hernias is still controversial and yet to be accepted even amongst pediatric surgeons expert in laparoscopy.
Keywords: herniotomy; herniorrhaphy; minimal invasive surgery; Europe